2016
DOI: 10.1103/physrevapplied.6.024017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Free Liquid-Helium Recovery Plants: The Solution for Low-Temperature Flow Impedance Blocking

Abstract: The blocking of fine-capillary tubes used as flow impedances in 4 He evaporation cryostats to achieve temperatures below 4.2 K is generally attributed to nitrogen or air impurities entering these tubes from the main bath. The failure of even the most rigorous low-temperature laboratory best practices aimed at eliminating the problem by maintaining the cleanliness of the helium bath and preventing impurities from entering the capillary tubes suggests that a different cause is responsible for the inexplicable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…With a boiling point of 4.2 K at 100 KPa, liquid helium is the coldest fluid that exists in nature. Below its critical temperature (Tc = 5.2 K), any unwanted substance present in the liquid phase, that is, any impurity, will be in solid form, resulting in mist, snow, suspensions or particulates [6]. The vapor pressure of these solid impurities will be, in general, negligibly small (<<10 −9 Pa), except for the case of the hydrogen isotopes and their molecular combinations [7] for which this is of the order of 10 −2 Pa and 10 −5 Pa, at 5.2 and 4.2 K, respectively.…”
Section: Liquid Helium Puritymentioning
confidence: 99%
“…With a boiling point of 4.2 K at 100 KPa, liquid helium is the coldest fluid that exists in nature. Below its critical temperature (Tc = 5.2 K), any unwanted substance present in the liquid phase, that is, any impurity, will be in solid form, resulting in mist, snow, suspensions or particulates [6]. The vapor pressure of these solid impurities will be, in general, negligibly small (<<10 −9 Pa), except for the case of the hydrogen isotopes and their molecular combinations [7] for which this is of the order of 10 −2 Pa and 10 −5 Pa, at 5.2 and 4.2 K, respectively.…”
Section: Liquid Helium Puritymentioning
confidence: 99%
“…In 2016, Gabal et al [4] and, also in a recent paper, Will et al [9], it was reported that even hydrogen concentrations within parts per billion are sufficient to block the helium flow within a few hours of operation. On the other hand, hydrogen impurities in liquid helium are easy to detect using a dedicated sensor developed at the University of Zaragoza [4]. It consists of a test capillary that is connected to a vacuum pump (see figure 2 in reference [10]) and has been successfully tested elsewhere [9].…”
Section: Introductionmentioning
confidence: 97%
“…This points to hydrogen as the source of blocking. Many research laboratories around the world have faced this issue at a considerable financial cost because the affected systems have to be warmed up to room temperature to recover their typical low-temperature operation performance [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%